Analysis of The Effect of Gender on High School Students' Misconceptions - Kristyasari, Marantika Lia; Pongkendek, Jesi Jescen (Department of Chemistry Education, Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
Misconceptions are a problem always faced in education, one of which is in the field of science, especially in chemistry. One of the chemical materials that students consider pretty challenging to understand because it is abstract, making it possible for misconceptions to occur, is chemical bonding. Misconceptions among students need to be identified quickly so they can be addressed immediately so they do not interfere with further learning. This research aims to determine the relationship between gender and the misconceptions of SMA YPK in Merauke Regency regarding chemical bonding material. Research data was analyzed quantitatively descriptively using the Polytomus Rasch Model. The respondents in this study were 76 Class X high school students who were selected using simple random sampling with 46 female and 30 male students. The research results showed that male students' average percentage of misconceptions was 31.9% (medium category), and female students were 18.6% (low type). The question indicators show that the highest percentage of misconceptions is in the question indicator for determining valence electrons; male students are 60% (medium category), and female students are 49% (medium type). Based on the overall misconception results regarding chemical bond indicators, gender influences the level of misconceptions of high school students in the city of Merauke.